2018
DOI: 10.1159/000488472
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Suppresses Ocular Inflammation by Inhibiting the Activation of NF-κβ Pathway in Endotoxin-Induced Uveitis

Abstract: Background/Aims: Lipocalin 2 (LCN2), an important mediator of a variety of cellular processes, is involved in regulating the inflammatory response, but its roles in different inflammatory diseases are controversial. Because the role of LCN2 in ocular inflammation has been unclear until now, we explored the function of LCN2 in lipopolysaccharide (LPS)-induced ocular inflammation in vivo and in vitro. Methods: Endotoxin-induced uveitis (EIU) was induced in male Sprague Dawley rats by the intravitreal injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 43 publications
(52 reference statements)
5
30
0
Order By: Relevance
“…It has been reported that LCN2 participates in light-induced photoreceptor death [46] and the development of early AMD [47]. However, other studies have shown that LCN2 is also involved in retinal pro-survival and anti-oxidative responses [42] and can suppress inflammation and reduce retinal degeneration [41,42]. In this study, we observed a significantly higher plasma level of LCN2 in nAMD patients with macular fibrosis, suggesting its potential pro-fibrotic roles.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It has been reported that LCN2 participates in light-induced photoreceptor death [46] and the development of early AMD [47]. However, other studies have shown that LCN2 is also involved in retinal pro-survival and anti-oxidative responses [42] and can suppress inflammation and reduce retinal degeneration [41,42]. In this study, we observed a significantly higher plasma level of LCN2 in nAMD patients with macular fibrosis, suggesting its potential pro-fibrotic roles.…”
Section: Discussionsupporting
confidence: 52%
“…Plasma and urine levels of LCN2 have been used as a biomarker for kidney disease [38,39] and cancer progression [40]. Recent studies have shown that retinal cells including Müller glia [41][42][43], microglia and RPE [43,44] can all express LCN2 and the expression is upregulated under stress conditions [41,43,45]. Furthermore, increased LCN2 have been observed in patients with Stargardt disease, retinitis pigmentosa, and AMD [42].…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to the question of whether there an intermediate regulatory factor between LCN2 and NF-κB or whether LCN2 acts directly on transcriptional activation 42 . When the IP assay was performed using an endogenous LCN2 antibody and SFBfusion-LCN2, weak binding of LCN2 to NF-κB was observed, suggesting a regulatory factor between LCN2 and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Parmar's in vitro data, LCN-2-mediated regulation of NF-κB activation has also been documented in inflammation during progression of endotoxin-induced uveitis, a well-established model of acute ocular inflammation. LCN-2 was significantly upregulated in the retinae of the rats after induction of uveitis, and played a protective antiinflammatory role by negative regulation of phosphorylation and nuclear translocation of NF-κB p65 in Muller cells and retinal tissues [90]. An earlier study conducted using eyes from horses suffering from autoimmune equine recurrent uveitis also reported upregulation of LCN-2 expression compared to healthy eyes.…”
Section: Role Of Lcn-2 In Ocular Diseases: Focus On Age-related Maculmentioning
confidence: 86%
“…6) and in a mouse model ( Fig. 7) with AMD-like pathology [89][90][91][92]. One of the easiest ways to induce retinal degeneration is to expose dark-adapted animals to high-intensity fluorescent light right after chemical pupil dilation [89,93].…”
Section: Role Of Lcn-2 In Ocular Diseases: Focus On Age-related Maculmentioning
confidence: 99%